Under the Background of High-Quality Development, the Influence of Creating the Cultural Symbol of ‘Shaanxi Drama’ on Shaanxi’s Economic Development (Journal of Global Humanities and Social Sciences, 2024)
As an ancient capital of the thirteen dynasties, Shaanxi Province has been striving to create an “international tourism destination of Chinese ancient capital culture.” In recent years, the development trend is good, and tourism performing arts have made great contributions to this, which has greatly improved Shaanxi Province, especially Xi’an, as a popular tourist destination. As a new business card of Shaanxi, it is of great significance to study what kind of cultural symbol it will create, which will become a new bright spot of Shaanxi tourism and further promote the development of the Shaanxi economy.